Hormonal function after ovarian transposition to the abdominal subcutaneous fat tissue. Issue 1 (1st January 2006) - Nagao, S.; Fujiwara, K.; Ishikawa, H.; Oda, T.; Tanaka, K.; Aotani, E.; Kohno, I.
Abstract : We previously reported a new technique for ovarian transposition to the abdominal subcutaneous fat tissue (OTAFT) following hysterectomy. The purpose of this study is to assess the hormonal function after OTAFT. From 1993 to 2000, OTAFT was performed in 27 patients (group A). Forty-two women underwent hysterectomy and retained ovaries without transposition (group B). In 19 cases, bilateral oophorectomy with hysterectomy was performed, and they received a hormone replacement therapy (HRT) (group C). Serum follicle-stimulating hormone (FSH) level of patients was monitored every 2–12 months, and the time of menopause (defined as FSH >40 mIU/mL two times consecutively) was determined in groups A and B. After a median follow-up of 65 months, cumulative ovarian survival did not show significant difference between group A and group B (HR = 0.52, 95% CI = 0.17–1.16; P = 0.10). In patients who were 40 years old or younger, ovarian function declined significantly in group A compared to group B (HR = 0.29, 95% CI = 0.02–0.91; P = 0.04). However, FSH level of postmenopausal patients in group A was not different from FSH level of patients in group C, but FSH level of postmenopausal patients in group B was significantly higher than FSH level of patients in group C ( P = 0.002). Although the procedure of OTAFT may somewhat affect the ovarian function, the transposed ovary in postmenopausal women presumably still secrete a small amount of estrogen which is equivalent to an estrogen level by HRT.